2010
DOI: 10.1038/jcbfm.2010.55
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of [11C]AZ10419369 Binding to 5-HT1B Receptors in Human Brain

Abstract: A novel radioligand for positron emission tomography (PET) imaging of serotonin 5-HT1B receptors, [11C]AZ10419369, has been recently described. In this study, the potential for quantitative analysis of [11C]AZ10419369 binding to central 5-HT1B receptors was evaluated in human subjects. PET measurements were performed after injection of [11C]AZ10419369 in 10 subjects. Data were analyzed with kinetic modeling and linear graphical analysis using the arterial plasma as input function, and with reference tissue mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 39 publications
(58 reference statements)
5
43
0
Order By: Relevance
“…Previously, we reported that [ 11 C]AZ10419369 is suitable for in vivo quantification of 5-HT 1B receptors in the brain of monkey and man (Pierson et al, 2008;Varnäs et al, 2011a). Of the 14 serotonin receptors, the 5-HT 1A and the 5-HT 1B receptor are the two receptors located presynaptically (Barnes and Sharp, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that [ 11 C]AZ10419369 is suitable for in vivo quantification of 5-HT 1B receptors in the brain of monkey and man (Pierson et al, 2008;Varnäs et al, 2011a). Of the 14 serotonin receptors, the 5-HT 1A and the 5-HT 1B receptor are the two receptors located presynaptically (Barnes and Sharp, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In a collaboration between Karolinska Institutet and AstraZeneca, a 5-HT 1B receptor selective compound, AZ10419369, has recently been labeled with carbon-11 ) and characterized as a suitable radioligand for quantification of 5-HT 1B receptor binding in the human brain in vivo (Varnäs et al 2010). This radioligand now represents a promising tool for quantification of receptor occupancy induced by compounds targeting the 5-HT 1B receptor.…”
Section: Introductionmentioning
confidence: 99%
“…The examination with PET and [ 11 C]AZ10419369 was performed as previously described (Varnas et al, 2011). The mean (6s.d.)…”
mentioning
confidence: 99%
“…The cerebellum was chosen as reference region, due to its negligible 5-HT 1B receptor density (Varnas et al, 2001), and defined manually. The simplified reference tissue model has been validated for calculation of [ 11 C]AZ10419369 BP ND in humans (Varnas et al, 2011) and was applied within Matlab R2007b for Windows.…”
mentioning
confidence: 99%